Cultivable mushroom growth‑promoting bacteria and their impact on Agaricus blazei productivity - Young, Li-Sen; Chu, Jiunn-Nan; Hameed, Asif; Young, Chiu-Chung (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to identify growth‑promoting bacteria isolated from Agaricus blazei and to evaluate their effect on mushroom mycelial growth and productivity. A total of 56 A. blazei‑associated bacterial isolates were obtained from casing soil and identified by 16S rRNA gene sequencing. Bacteria were evaluated as to phosphate‑solubilization ability, nitrogen‑fixation capability, and secretion of cellulase. Superior isolates were tested for their to effect on A. blazei productivity, micelial growth, and on the contents of the polysaccharide‑protein complex and of N, P, K, Ca, and Mg. Bacterial isolates were identified as actinobacteria (60%), firmicutes (20%), and proteobacteria (20%). Among them, ten isolates had phosphate‑solubilization ability, eight showed nitrogen‑fixation capability, and 12 isolates promoted A. blazei mycelium growth. Bacterial inoculation reduces time till harvest in up to 26 days, increases fresh mushroom yield up to 215%, and increases total polysaccharide‑protein complex content twofold when compared to the non‑inoculated control. The actinobacteria group is the predominant A. blazei‑associated phylum.